Linhas que separam, linhas que unem: percepção de fronteira na cidade de Cáceres - MT - Targioni, Paolo (2020)
The present study desires to investigate the perception that residents of a border region between Brazil and Bolivia have about the physical border that separates the two countries, as well as other borders that may possibly exist. Initially, in order to support empirical research, were analyzed the work of some of the most important border studies authors. Subsequently, we applied a questionnaire to young students from a university campus in the city of Cáceres (Mato Grosso - Brazil) and then, with the same corpus, were formed focus groups in order to deepen the understanding of the obtained results. The city has been chosen because of its geographical particularity: close enough to the border, so that its residents can get to know it, but also far, to the point that there are people living there who have never approached it. This characteristic meant that the population of the study was composed of people who know the border region very well and others who only have a vague and remote idea, often result of prejudices and stereotypes. Based on the theoretical writings of Sandro Mezzadra on the indeterminacy of the border as well as other authors considered as a reference on border studies, the objective was to better understand if there would be a difference between those who well experienced the physical border and those who do not know it, as in the perception of that, as well as in the perception of other borders (such as gender or ethnic-racial ones) that may eventually arise in our daily lives. The results achieved confirmed the difference in the perception of the indeterminacy of the physical boundary, between the familiar and the unfamiliar with the border, but did not provide significant data relatively the perception of other forms of boundaries. Another important question concerned how would develop the relationship between indigenous residents and those living across the border: foreigners. We were interested in understanding whether there was any difference in this relationship with foreigners between those who know and those who do not know the border, as well as between residents of an urban and a rural area. These hypotheses also were tested through the same interviews, questionnaires and focus groups. The final results, which showed no substantial differences in the relationship with foreigners between those who know and do not know the border, confirmed a different relationship between rural and urban residents.